Hubungan Keterampilan Sosial dan Kepercayaan Diri Peserta Didik Kelas VIII di SMPN 8 Yogyakarta - Dewantari, Tri; Masya, Hardiyansyah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
Social skills and self-confidence are two things that are interrelated. In junior high school students who have social skills and confidence is very important for learners. The research design uses correlation design. The researchers collected data on social enlightenment and self-confidence using the scale of skills and social beliefs that had been tested for their validity and reliablity. The subjects used in this study were 158 students at SMPN 8 Yogyakarta taken through random sampling technique from the population as much. The results of data processing showed that most of the students of grade VIII SMPN 8 Yogyakarta had high social and confidence skills, and data analysis showed that there was a relationship between social skills and students' self-confidence.